Knowing reality a guided introduction to metaphysics and epistemology - Moore, Dwayne 1975- (Broadview Press, 2023)
"Knowing Reality is a guided introduction to metaphysics and epistemology. Each of the book's twelve chapters contains extended excerpts from influential historical and contemporary philosophers, as well as a guided exposition of their views and their locations within the logical space of the issues at play. Topics are introduced through engaging thought experiments, with relevant philosophical puzzles sprinkled throughout. Complex issues are explained using down-to-earth examples, with illustrations provided to connect with readers and assist them in understanding the sophisticated concepts under discussion."--